Insights into the development of hepatocellular fibrillar inclusions in European flounder (Platichthys flesus) from UK estuaries. (October 2020) - Bignell, John P.; Barber, Jon; Bateman, Kelly S.; Etherton, Mark; Feist, Stephen W.; Galloway, Tamara S.; Katsiadaki, Ioanna; Sebire, Marion; Scott, Alexander P.; Stentiford, Grant D.; Bean, Tim P.
Abstract: Hepatocellular fibrillar inclusions (HFI) are an unusual pathology of unknown aetiology affecting European flounder ( Platichthys flesus ), particularly from estuaries historically impacted by pollution. This study demonstrated that the HFI prevalence range was 6–77% at several UK estuaries, with Spearman rank correlation analysis showing a correlation between HFI prevalence and sediment concentrations of ∑PBDEs and ∑HBCDs. The data showed that males exhibit higher HFI prevalence than females, with severity being more pronounced in estuaries exhibiting higher prevalence. HFI were not age associated indicating a subacute condition. Electron microscopy confirmed that HFI were modified proliferating rough endoplasmic reticulum (RER), whilst immunohistochemistry provided evidence of VTG production in HFI of male P. flesus . Despite positive labelling of aberrant VTG production, we could not provide additional evidence of xenoestrogen exposure. Gene transcripts (VTG/CHR) and plasma VTG concentrations (>1 μg ml −1 ), were only considered elevated in four male fish showing no correlation with HFI severity. Further analysis revealed that reproductively mature female P. flesus i.e. >3-year-old, did not exhibit HFI, whereas males of all ages were affected. This, combined with previous reports that estradiol (E2) can impair mixed function oxygenase activity, supports a hypothesis that harmful chemical metabolites (following phase 1 metabolism of their parent compounds) are potentially responsible for HFIs observed in male and ≤ 3-year-old female fish. Consequently, HFI and xenoestrogenic induced VTG production could be independent of each other resulting from different concurrent toxicopathic mechanisms, although laboratory exposures will likely be the only way to determine the true aetiology of HFI. Highlights: Hepatocellular fibrillar inclusions (HFI) occur in flounder from UK estuaries. HFI in male flounder were not age associated indicating a subacute condition. Reproductively mature female flounder i.e. >3-year-old, did not exhibit HFI. HFI in males always labelled positive for vitellogenin using immunohistochemistry. HFI prevalence correlated to sediment concentrations of ∑PBDEs and ∑HBCDs.